Aspek Yuridis Undang-Undang Jabatan Notaris Nomor 30 Tahun 2004 jo UU Nomor 2 Tahun 2014 terhadap Kinerja Notaris - Henny Tanuwidjaja (Jurnal Hukum, 2014)
AbstractÂ Â Â Â Â Â Â Â Â Â Â  The Government of the Republic of Indonesia in its efforts to improve the performance of a notary in Indonesia, reflected by the enactment of Law Notary No. 30 of 2004 on October 6, 2004 in exchange for Notary Regulation colonial products, and then because of the changing times and the needs of law that have not been accommodated, so that the necessary adjustment, some chapters of UUJN Number 30 Year 2004, then the enactment of Indonesian Republic Laws Number 2 Year 2014 concerning Notary (hereinafter referred UUJN), and entered into force on January 15th, 2014, wherein the arrangement also supervise the performance of the notary who made the Minister of Law and Human Rights R.I, in this case implementation oversight is monitoring by the the Supervisory Council of the Association of Notaries Indonesia, overall it is the device legislation to regulate and supervise the performance of Notary in Indonesia,Â Â Â Â Â Â Â Â Â Â Â  Notary is a public official should have several characteristics inherent in their duties, among others: responsibility, discipline, quality of work, morality and code of professional conduct, skills also his duty in this case related to "apprenticeship" which is one of the requirements absolute to be appointed as a Notary. Notaries are figures of human resources which runs most of the state administration in the field of civil law, so that if a country is not supported by the resources of qualified notary, then it will be one of the factors inhibiting the development of the national economy or global economic.Â Â Â Â Â Â Â Â Â Â Â  Law Notary Public service users, consider the deeds of Notary trust worthy and can serve as strong evidence in case of a legal dispute in court and expects to provide legal certainty guarantee for the correctness of the contents of the deed he had done, because the notary service users assume that notary much more to understand and master the field of science, so that people feel safe if desired intent will be poured right into authentic deed that made by notary who self-selected by themselves, because of the belief in the quality of science and performance. Â Â Â Â  However, there was found the case against the notary deed material legally flawed, because it is less understood material Franchise Agreement are regulated by Government Regulation Number 42 Year 2007. Therefore, the Notary has been sued under section 372 KUH Pidana KUH Perdata dan 1365. by franchiseâ€™s owner, because they feel aggrieved, then through court Surabaya with number lawsuit: 475/ PDT.G/2014/ PN.Sby dated June 10, 2014. In which case the author at present as an expert witness.Â Â Â Â Â Â Â Â Â Â Â  With the government's readiness to regulate and advance the performance of Notary through UUJN and implementation supervision conducted by the Supervisory Council in this case Indonesian Notaries Association (INI), aims and expected to provide improved quality of work and minimize mistakes that made by Notary, but how effectively setting U.U.J.N and Notary code of Ethics also supervision by the Board of Trustees to the quality performance of notaries? From the research, the authors obtain the evidence is less satisfactory to the performance of the Notary and concluded a few things short comings as follows:1.Â Â Â Â Â  Notary performance that served to open the office with work experience under 5 (five) years, is still far from satisfactory service users in certain authentic deed;2.Â Â Â Â Â  A number of respondent who have been contected by the auther, more then 50% less than satisfactory performance of the new Notary,even itâ€™s harmful if used;3.Â Â Â Â Â  Internship for prospective notary can be seen from (2) opinions: the first for a notary public employees who have worked at the notary's office for many years of apprenticeship provisions, arrangement (2) year internship is not a problem. But for pure student graduates Master Notary that the field work everyday with a different scope of notaryâ€™s work,for example it as housewives or as employees, according the authors, thatâ€™s less enough experience and still far of good performance. Keywords: Law Notary (UUJN), Notary Code of Ethics, Performance Notary.Â AbstrakPemerintah Republik Indonesia dalam upayanya meningkatkan kinerja notaris di Indonesia, tercermin dengan diundangkannya Undang-Undang Jabatan Notaris (UUJN) Nomor 30 Tahun 2004 pada tanggal 06 Oktober 2004 sebagai ganti Peraturan Jabatan Notaris produk peninggalan kolonial dan kemudian karena perkembangan zaman dan kebutuhan hukum yang belum tertampung, sehingga perlu penyesuaian. Beberapa pasal UUJN Nomor 30 Tahun 2004 tersebut, kemudian diundangkannya UU Nomor 2 Tahun 2014 tentang Jabatan Notaris (selanjutnya disebut U.U.J.N), dan mulai diberlakukan sejak tanggal 15 Januari 2014, yang di dalamnya tercakup pula pengaturan pengawasan terhadap kinerja notaris yang dilakukan oleh Menteri Hukum dan HAM R.I dalam hal ini pelaksanaan pengawasannya dibantu oleh Majelis Pengawas Notaris yaitu Ikatan Notaris Indonesia, keseluruhan ituÂ  merupakan upaya pemerintah menyiapkan perangkat undang-undang untuk mengatur dan mengawasi kinerja notaris di Indonesia,Â Â Â Notaris adalah pejabat umum yang seharusnya melekat beberapa karakteristik dalam menjalankan tugasnya, antara lain: tanggung jawab, disiplin, mutu kerja, moralitas dan kode etka profesi, juga ketrampilan menjalankan tugas jabatannya yang dalam hal ini berkaitan dengan â€œmagang kerjaâ€ yang merupakan salah satu syarat mutlak untuk diangkat sebagai notaris. Notaris adalah figur-figur sumber daya manusia yang menjalankan sebagian administrasi negara dalam bidang hukumÂ  keperdataan, sehingga apabila suatu negara tidak didukung sumber daya notaris yang berkualitas, maka akan menjadi salah satu faktor penghambat perkembangan ekonomi nasional maupun era global.Masyarakat pengguna jasa hukum notaris, menganggap akta-akta yang dibuat di hadapan notaris dapat dipercaya dan dapat dijadikan sebagai alat bukti yang kuat apabila terjadi sengketa hukum di pengadilan dan mengharapkan akan memberikan jaminan kepastian hukum atas kebenaran isi akta yang dibuatnya, karena masyarakat pengguna jasaÂ  notaris menganggap notaris jauh lebih mengerti dan menguasai bidang ilmunya, sehingga masyarakat merasa aman jika maksud yang dikehendaki akan dituangkan dengan benar ke dalam akta otentik yang dibuat notaris yang dipilih sendiri, karena kepercayaan akan kualitas ilmu dan kinerjanya.Namun demikian masih dijumpai kasus gugatan terhadap akta notaris yang materi aktanya cacat hukum, karena dalam kasus ini kurang dipahaminya materi Perjanjian Waralaba (Franchise) yang diatur oleh Peraturan Pemeritah Nomor 42 Tahun 2007. Sehingga Notaris tersebut digugat berdasarkan pasal 1365 KUHPerdata dan 372 KUH Pidana oleh pemilik franchise karena merasa dirugikan, melalui P.N Surabaya dengan No.Gugatan 475/PDT.G/ 2014/ PN.Sby.Tanggal 10 Juni 2014, dimana penulis di hadirkan sebagai saksi ahli.Â Â Â Â Â Â Â Â Â Â Â  Dengan kesiapan pemerintah untuk mengatur dan memajukan kinerja notaris melalui U.U.J.N serta pelaksanaan pengawasannya yang dilakukan oleh Majelis Pengawas, seberapa efektif pengaturan UUJN dan Kode Etik Notaris terahadap kualitas kinerja notaris? Dari hasil penelitian penulis menyimpulkan beberapa hal kekurangannya : Â Â Â Â Kinerja notaris yang bertugas membuka kantor dengan pengalaman kerja di bawah 5 (lima) tahun, masih jauh dari memuaskan pengguna jasa dalam pembuatan akta otentik tertentu;Dari responden yang penulis hubungi, lebih dari 50 % kinerja notaris baruÂ  kurang memuaskan, bahkan merugikan jika dipergunakan;Magang bagi calon notaris tidak berfungsi maksimal.Kata kunci: Undang-Undang Jabatan Notaris (UUJN), Kode Etik Notaris, Kinerja Notaris.